Gari Muju Desa Wisata Budaya - ., Minardi; Firdaus, Mohamad; Winarti, Safitri Endah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Gari has long been famous for its Argo Wijil Culinary Market which is managed by BUMKal (Business Entity Owned by Kalurahan) Mardi Gemi. BUMKal Mardi Gemi plans to make new breakthroughs and innovations in the world of tourism. Gari, which is located near the center of the Regency Capital, namely Wonosari, does not allow selling nature tourism, because it does not have much natural potential. Opportunities then lead to Cultural Tourism by making Gari a Cultural Tourism Village. This Community Service Program aims to encourage Gari as a Cultural Tourism Village. Data collection methods include field observations to identify cultural potential, conduct in-depth interviews with various related parties, then study literature to strengthen the tourism component-4A (Attractions, Accessibility, Amenity, Ancilliary) and the concept of cultural tourism village. Furthermore, the data is analyzed starting from an inventory of customs, artistic potential, traditional knowledge, traditional technology, and Javanese architecture. This data analysis then became the basis for the Preparation Phase I (First). Of the nine hamlets in Kalurahan Gari, each has its own cultural potential. This potential includes customs, such as apostleship, sending donga and besik kali; artistic potential, such as: tayub, karawitan, mocopat, bregodo, doger art, thek-thek art, garangan art, traditional knowledge and traditional technology, such as: wayang making, gamelan making, wasp sauce culinary, bonggol chips culinary, chili sauce culinary, traditional massage, blacksmithing, and making tempeh. Currently, Gari has been promoted from the Cultural Pockets Pioneer Village to the Cultural Pilot Village. Preparation Phase II (Second) Gari needs to go to Prima Village and Preneur Village which actually already has capital.